The importance of dance for the cognitive function of people with Parkinson's: A systematic review with meta-analysis - Gil P.R.* (2024)
© 2024 Elsevier LtdObjective: Investigate the effectiveness of dance intervention to provide evidence of its effects on cognition in people with Parkinson's. Methods: A study registered in PROSPERO (CRD42023474696), with searches carried out electronically in five databases (PubMed Central®, Embase, Web of Science, ScienceDirect, and Scopus Elsevier), over the last 10 years. The risk of bias was assessed using the Cochrane collaboration scale (RoB2 and ROBINS-I). Results: The studies presented ‘’low’’ and ‘’moderate’’ risks of bias. The instruments to assess cognitive function were heterogeneous. The dance modalities used were named dance training, dance-physiotherapy, Brazilian samba, dance, Sardinian folk dance, dance therapy, and tango. Eleven studies were included in the review and the meta-analysis showed high heterogeneity (I2 = 90%; p < 0.0001). The analysis with 6 studies that used the same cognitive screening instrument (MoCA) showed low heterogeneity (I2 = 0%; p = 0.41). The funnel plot presents the studies in a dispersed manner, which suggests publication bias.